Influence of tinnitus on pain severity and quality of life in patients with temporomandibular disorders (Journal of Applied Oral Science, 2012)
OBJECTIVE:The aim of this cross-sectional study was to evaluate the relationship among pain intensity and duration, presence of tinnitus and quality of life in patients with chronic temporomandibular disorders (TMD). MATERIAL AND METHODS: Fifty-nine female patients presenting with chronic TMD were selected from those seeking for treatment at the Bauru School of Dentistry Orofacial Pain Center. Patients were submitted to the Research Diagnostic Criteria anamnesis and physical examination. Visual analog scale was used to evaluate the pain intensity while pain duration was assessed by interview. Oral Health Impact Profile inventory modified for patients with orofacial pain was used to evaluate the patients' quality of life. The presence of tinnitus was assessed by self report. The patients were divided into: with or without self report of tinnitus. The data were analyzed statistically using the Student's t-test and Pearson's Chi-square test, with a level of significance of 5%. RESULTS: The mean age for the sample was 35.25 years, without statistically significant difference between groups. Thirty-two patients (54.24%) reported the presence of tinnitus. The mean pain intensity by visual analog scale was 77.10 and 73.74 for the groups with and without tinnitus, respectively. The mean pain duration was 76.12 months and 65.11 months for the groups with and without tinnitus, respectively. The mean OHIP score was 11.72 and 11.74 for the groups with and without tinnitus, respectively. There was no statistically significant difference between groups for pain intensity, pain duration and OHIP scoreS (p>;0.05). CONCLUSION: Chronic TMD pain seems to play a more significant role in patient 's quality of life than the presence of tinnitus.